Kontribusi Katekese Bagi Ekoteologi dalam Perspektif Petunjuk untuk Katekese 2020 - Rota, Laurentius (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2025)
This study examines the intersection of catechesis and ecotheology, a movement promoting a harmonious relationship between God, humanity, and the environment. This alignment is particularly timely, given the Indonesian Ministry of Religious Affairs' 2025 Priority Program aimed at addressing the ecological crisis. Identifying the root of environmental degradation as an anthropocentric worldview that fosters nature’s exploitation, this research advocates for a shift toward a partnership model. Central to this transition is the 2020 Directory for Catechesis (DC), which introduces a novel focus on ecological responsibility in articles 381–384—a theme notably absent in previous directories. Utilizing a qualitative content analysis of the DC 2020 and contemporary literature, the study categorizes and interprets key themes to determine how catechesis reinforces ecotheology. The findings reveal a dual contribution: theoretical and practical. Theoretically, catechesis bolsters the biblical foundations of ecotheology and facilitates a mental shift away from anthropocentrism. Practically, it encourages the habituation of environmentally friendly behaviors and the development of ecological catechetical programs. Ultimately, the study concludes that catechesis is a vital pastoral pathway for fostering spiritual consciousness and sustainable lifestyles. By enriching the discourse on ecotheology through a pastoral lens, this research highlights catechesis as an essential tool for both internal mentality change and concrete environmental action.